Face yoga – or just marketing in facial aesthetics (Journal of Face Aesthetics, 2025)
Facial yoga is a contemporary type of activity offered for maintaining a youthful, aesthetic appearance of the face and its skin.The aim of this study is to analyse a number of facial yoga videos available on YouTube in terms of their methodological layout and how they relate to the classical Indian yoga system.The method of the study is to analyse three Polish-language recordings of Facial Yoga. The criterion for selection was the proposed exercise time for viewers - approximately 10 minutes.The research material consisted of quantitative variables (total number of exercises, time or number of repetitions of the exercises, occurrence of additional methods of working with facial structures) and qualitative variables (correct anatomical nomenclature, methodical presentation of the exercises, discussion of indications and contraindications to the use of a given exercise).The results of the analysis of the research material indicate the methodical correctness of the description, demonstration and technique of the exercise. All analysed films are characterised by a methodical transition from the forehead towards the chin (cephalocaudally). The sets of exercises in the individual videos are highly varied; additional techniques related to cosmetology or physiotherapy are also used.Difficulties pointed out by authors of scientific papers on facial yoga classes indicate the need to develop and standardise an exercise methodology to answer the question of its effectiveness in preserving the youthful appearance of the face. It should be stated that the use of the name facial yoga appears to be unauthorised.
Keywords: none